Japan Overseas Cooperation Volunteers (JOCVs) in the Philippines: Motivations, challenges, strategies and benefits gained - Tsubotani, Maria Vilma M. (Animo Repository, 2003)
This study describes the motivations, challenges encountered, strategies employed and benefits gained by the Japan Overseas Cooperation Volunteers (JOCVs) in the Philippines. Primarily descriptive, interview method, with an aid of interview guide, was employed to gather pertinent data. Twenty-four male and female respondents dispatched in different areas of the country, and who were into various fields of expertise constituted the subjects. Results showed that the respondents were driven by personal, altruistic, social, religious, educational and economic motivations. The challenges encountered were social, cultural and administrative in nature. To offset the challenges encountered, strategies were employed which included learning the local language, appreciation of culture, initiating orientation, doing alternative tasks and spending some personal resources. The benefits achieved included enhanced communication, appreciation of local culture, gained a network of friends and self-exploration. It is concluded that the young Japanese now regard volunteering in the same manner as work and leisure. They get involved simply because they felt they want to try something different or the activities looked interesting. Volunteering is no longer the ideal of making a commitment to the community or to the society.